2005
DOI: 10.1088/0957-0233/16/3/003
|View full text |Cite
|
Sign up to set email alerts
|

Laser Doppler profile sensor with sub-micrometre position resolution for velocity and absolute radius measurements of rotating objects

Abstract: We have investigated the application of a laser Doppler profile sensor for simultaneous measurement of position and velocity on moving rough surfaces. It is shown that, with this technique, the shape of rotating workpieces and components, e.g., turbine blades or turning parts, can be measured absolutely and in-process with only one single sensor. Measurements on different surfaces with defined shape and roughness are presented. The obtained minimum uncertainty in the position is about 250 nm in the centre of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 18 publications
0
66
0
6
Order By: Relevance
“…The relative standard uncertainty of the velocity measurement σ v /v has been proven to be a constant factor of approximately σ v /v ≈ 10 −3 [11], [10], [12]. Thus, (5a) and (5b) can be expressed by…”
Section: Emulating Blade Vibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative standard uncertainty of the velocity measurement σ v /v has been proven to be a constant factor of approximately σ v /v ≈ 10 −3 [11], [10], [12]. Thus, (5a) and (5b) can be expressed by…”
Section: Emulating Blade Vibrationmentioning
confidence: 99%
“…We invented a laser Doppler distance sensor (LDDS) that measures the tip clearance and the tangential blade tip velocity simultaneously [10], [11], [12]. The measurement principle of the LDDS relies on an extension of the laser Doppler velocimeter and is depicted in Fig.…”
Section: Novel Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…which is also monotonously varying and does not depend on the velocity v. The inverse function z(q) can therefore be used to determine the axial position z of a scattering object inside the measurement volume 6 . With the known z-position, the actual fringe spacings d 1 and d 2 can be identified via the calibrated fringe spacing curves d 1,2 (z).…”
Section: Principle Of the Laser Doppler Position Sensormentioning
confidence: 99%
“…In this contribution, we present a novel laser Doppler position sensor, which allows simultaneous measurement of axial position and tangential velocity of fast rotating objects offering high temporal resolution and high position resolution *thorsten.pfister@tu-dresden.de; phone: +49 351 463-35303; fax: +49 351 463-37716; http://eeemp1.et.tu-dresden.de/ "iitiq •0 simultaneously [6][7][8] . It will be shown that, in contrast to conventional distance measurement techniques, the position uncertainty of this sensor is in principle independent of the object velocity since the determination of the position is attributed to a Doppler frequency measurement.…”
Section: Introductionmentioning
confidence: 99%